Taxation of Digital Advertising Services: Indonesia’s Policy Response and Global Relevance (Indonesian Tax Justice Review, 2025)
Digital advertising services generate substantial economic value in market jurisdictions without requiring physical presence. This paper analyzes Indonesia’s taxation of digital advertising services and its implications for tax justice. Using normative legal analysis, the study evaluates the application of VAT and withholding taxes to foreign digital advertising providers. The findings suggest that while Indonesia’s measures enhance short-term revenue collection, enforcement challenges persist due to cross-border complexity and limited international coordination. The paper argues that unilateral digital taxation measures offer partial solutions but cannot fully address structural inequities in taxing digital value creation. The global contribution of this study lies in providing a developing country perspective on taxing digital advertising revenues. Indonesia’s experience informs international debates on reallocating taxing rights in the digital economy and highlights the limitations of interim solutions. The study contributes to global tax justice scholarship by emphasizing the need for coordinated international reforms that prioritize market jurisdictions.